IDENTIFICATION OF DIGITAL EVIDENCE FACEBOOK MESSENGER ON MOBILE PHONE WITH NATIONAL INSTITUTE OF STANDARDS TECHNOLOGY (NIST) METHOD - Anton Yudhana; Imam Riadi; Ikhwan Anshori (Universitas Trunojoyo Madura, 2018)
Facebook Messenger is a popular social media. The increasing number of Facebook Messenger users certainly has a positive and negative impact, one of the negative effects is being used for digital crime. One of the sciences to get digital evidence is to do Digital forensics. Digital forensics can be done on a smartphone used by criminals. This research will carry out as much evidence of digital crime as possible from Facebook Messenger. In this study the forensic devices, Magnet AXIOM and Oxygen Forensics Suite 2014 were used using the National Institute of Standards Technology (NIST) method. NIST has work guidelines for both policies and standards to ensure that each examiner follows the same workflow so that their work is documented and the results can be repeated and maintained. The results of the research in the Magnet AXIOM and Oxygen Forensics Suite 2014 get digital evidence in the form of accounts, conversation texts, and images. This study successfully demonstrated the results of an analysis of forensic devices and digital evidence on Facebook Messenger. The results of the performance evaluation of forensic tools in the acquisition process using AXIOM Magnets are considered the best compared to Oxygen Forensics Suite 2014.